Postpandemic Stress Disorder among Health Care Personnel: A Cross-Sectional Study (Silesia, Poland) - Mateusz Grajek; Patryk Szlacheta; Karolina Sobczyk; Karolina Krupa-Kotara; Beata Łabuz-Roszak; Ilona Korzonek-Szlacheta (Behavioural Neurology)
Background. Postpandemic stress disorder (PPSD) is an unofficial term that refers to posttraumatic stress disorder (PTSD), a mental disorder resulting from increased stress, anxiety, and trauma associated with unpleasant life experiences. Many scientific studies indicate that symptoms of increased stress, job burnout, anxiety, and depressive disorders are associated with medical personnel performing their professional duties around COVID-19 patients. Objective. The purpose of this study was to assess the prevalence of symptoms that may indicate the presence of PPSD symptoms—depression, anxiety, and stress—in medical personnel. Material and Methods. The survey included 300 people, representatives of medical personnel. The group was divided into two sections. The first section numbered 150 and consisted of personnel in direct contact with COVID-19 patients (FR); the second group also consisted of 150 medical professionals, who but no longer directly involved in helping with COVID-19 cases (SR). The survey was conducted by indirect survey method using CAWI (computer-assisted web interview). The survey used a questionnaire technique. A proprietary tool enriched with standardized psychometric scales: BDI, GAD-7, FCV-19S, and PSS-10 was used. Kruskal-Wallis and Mann–Whitney U statistical tests were used in the statistical processing of the data. The probability level was 0.05. Results. Statistical inference made it clear that mental health problems that may indicate trauma are mainly present in the FR group. These symptoms decreased slightly in comparison between periods 2020 and 2021 (p<0.05). Conclusions. The COVID-19 pandemic significantly increased the prevalence of depression, anxiety, and stress among first responders. To ensure the psychological well-being of first responders, early assessment and care of mild depression, anxiety, and stress should be promoted to prevent the development of moderate and severe forms.